TOTEM DAN EKOKRITIK PADA TIGA CERPEN SENO GUMIRA AJIDARMA - Teguh Prasetyo; Anggino Tambunan (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
Abstract The exploitation of nature and its impact on animal extinction is a common occurrence due to excessive modernization. However, this issue is sometimes overlooked by the mainstream media and public discourse. In this case, literature often emerges to document or even voice criticism of the phenomenon of environmental destruction. Several works that voice criticism of the phenomenon of ecosystem destruction and animal extinction due to modern culture are the short stories of Seno Gumira Ajidarma (SGA). In this study, the author takes three SGA short stories entitled “Macan” (Tiger), “Cintaku Jauh di Pulau Komodo” (My Love is Far Away on Komodo Island), and “Badak Kencana” (Golden Rhinoceros). This study will be conducted using an ecocriticism approach, focusing on the examination of totems as key symbols in the three short stories. To dissect the meaning of totems, the concepts of totems, archetypes, and other concepts in Carl Gustav Jung's analytical psychology are also used. The findings of this study are that totems and their symbolism are narratives in short stories that voice criticism of the exploitation of nature and excessive hunting, which destroy the balance and culture of environmental preservation in the settings of the three short stories.